Plasmid recombination intermediates generated in a Saccharomyces cerevisiae cell-free recombination system. - Symington, L S (1985)
We have developed an assay utilizing Saccharomyces cerevisiae cell extracts to catalyze recombination in vitro between homologous plasmids containing different mutant alleles of the tet gene. Electrophoretic analysis of product DNA indicated that a number of novel DNA species were formed during the reaction. These species migrated through agarose gels as distinct bands with decreased electrophoretic mobility compared with the substrate DNA. The DNA from each individual band was purified and shown to be enriched 5- to 100-fold for tetracycline-resistant recombinants by using a transformation assay. The structure of the DNA molecules present in these bands was determined by electron microscopy. Recombination between circular substrates appeared to involve the formation and processing of figure-eight molecules, while recombination between circular and linear substrates involved the formation of molecules in which a circular monomer had a monomer-length linear tail attached at a region of homology.